Neural Computation For Flow Regime Classification Based On Electrical Capacitance Tomography. - Mat-Dan, A. A.; Mohamad-Saleh, J; Ahmad, M. A. (2004)
Recognition of gas-liquid flow regimes in pipelines is important in an industrial control process such as for oil production. In oil production, gas-liquid flows are normally concealed in a pipe the actual type of flows cannot be easily determined. Also, obtaining measurements corresponding to the flow distribution becomes almost impossible.